Does a Better Perfusion of Deconditioned Muscle Tissue Release Chronic Low Back Pain? - Valdivieso, Paola; Franchi, Martino V.; Gerber, Christian; Flück, Martin (Frontiers in Medicine, 2018)
Non-specific Chronic Low Back Pain (nsCLBP) is a multi-factorial condition of unknown etiology and pathogenesis. Physical and genetic factors may influence the predisposition of individuals to CLBP, which in many instances share a musculoskeletal origin. A reduced pain level in Low Back Pain patients that participate in exercise therapy highlights that disuse related muscle deconditioning may predispose individuals to nsCLBP. In this context, musculoskeletal pain may be the consequence of capillary rarefaction in inactive muscle as this would lower local tissue drainage and washing out of toxic waste. Muscle activity is translated into an angio-adaptative process, which implicates angiogenic-gene expression and individual response differences due to heritable modifications of such genes (gene polymorphisms). The pathophysiologic mechanism underlying nsCLBP is still largely unaddressed. We hypothesize that capillary rarefaction due to a deconditioning of dorsal muscle groups exacerbates nsCLBP by increasing noxious sensation, reducing muscle strength and fatigue resistance by initiating a downwards spiral of local deconditioning of back muscles which diminishes their load-bearing capacity. We address the idea that specific factors such as Angiotensin converting enzyme and Tenascin-C might play an important role in altering susceptibility to nsCLBP via their effects on microvascular perfusion and vascular remodeling of skeletal muscle, inflammation and pain sensation. The genetic profile may help to explain the individual predisposition to nsCLBP thus identifying subgroups of patients, which could benefit from "ad-hoc" treatment types. Future therapeutic approaches aimed at relieving the pain associated with nsCLBP, should be based on the verification of mechanistic processes of activity-induced angio-adaptation